2008
DOI: 10.1055/s-2007-1004827
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Duration of Active Labor in Nulliparous Women at Term

Abstract: We have assessed the independent predictors of duration of active labor in nulliparous women at term. Using a cohort of 1067 nulliparae in spontaneous labor at > 37.0 weeks with singleton fetuses in vertex presentation, multivariate analysis was used to identify independent predictors of duration of active labor. Duration of active labor was 4.1 +/- 2.4 hours. Stepwise linear regression selected 10 independent predictors of duration of active labor: gestational age at delivery ( P < 0.001), race ( P = 0.014), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 22 publications
0
20
1
Order By: Relevance
“…However, a high proportion of the sample received epidurals and/or induction with oxytocin, and the researchers made no attempt to adjust for these factors. Incerti et al found an association between gestational age and duration of active labor in nulliparous women at term but did not analyze birthweight [15]. We found evidence of collinearity between birthweight and gestational age, suggesting that the effect of gestational age is at least partially mediated by birthweight.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…However, a high proportion of the sample received epidurals and/or induction with oxytocin, and the researchers made no attempt to adjust for these factors. Incerti et al found an association between gestational age and duration of active labor in nulliparous women at term but did not analyze birthweight [15]. We found evidence of collinearity between birthweight and gestational age, suggesting that the effect of gestational age is at least partially mediated by birthweight.…”
Section: Discussioncontrasting
confidence: 51%
“…Although we have no way to offer proof, it is reasonable to assume that this relationship has more to do with the reasons or characteristics that led to oxytocin use, rather than its effects. Epidurals were also associated with longer conditional time, which can be related both to the indications for its use and to a negative effect on speed of labor [15, 17]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Incerti et al . reported on 1067 nulliparous women and found that a similar degree of variance ( R 2 = 0.51) in the length of labor could be determined with gestational age, maternal ethnicity, maternal risk factors, cervical dilatation, oxytocin use and epidural use as predictors in their model. Nesheim analyzed 5418 women in labor to assess the contribution of a variety of factors in predicting duration of labor, and found that the most significant predictors were nulliparity, induction vs spontaneous labor, neonatal birth weight, maternal height, gestational age and occipital position, but did not report overall variance.…”
Section: Discussionmentioning
confidence: 99%